DEVELOPMENT OF “FAMILY PANCASILA BOARD” POP-UP MEDIA FOR LEARNING PANCASILA VALUES IN GRADE III ELEMENTARY SCHOOL - Putri Permadani, Sholihatuzumna; Utama, Candra; Ayu Putri Viola, Wendy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to develop a Pop-Up learning medium entitled the "Family Pancasila Board" for teaching Pancasila Education to Grade III elementary school students. A Research and Development (RnD) methodology based on the ADDIE framework was adopted, consisting of five sequential phases: Analysis, Design, Development, Implementation, and Evaluation. The final product is a three-dimensional pop-up board that presents the symbols of Pancasila, the meaning of each principle, and illustrations of how Pancasila values can be practiced in everyday family life. Additionally, the media incorporates a QR-Code for accessing supplementary learning materials. Validation assessments from subject matter specialists, media experts, and end-users confirmed the media's appropriateness for classroom implementation. Material experts validated the product at 87.5%, media specialists at 85%, and teachers at an average of 89.3%. Practicality testing yielded exceptional results, with small-scale trials achieving 98% and large-scale trials reaching 96.8%, both categorized as "Very Practical." The developed media effectively enhances students' comprehension and motivation to implement Pancasila values in their family environments while fostering collaborative and engaging learning experiences.